2004
DOI: 10.1246/bcsj.77.73
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NaClO4 Concentration on the Two-Step Electroreduction of Zn2+ Ions in the Presence of Tetramethylthiourea

Abstract: The dependence of the two-step reduction of Zn2+ ions on NaClO4 and TMTU concentration at the dropping mercury electrode was examined. The catalytic activity of TMTU is related to both electron transfer steps and decreases in the order: 1 M NaClO4 > 0.5 M NaClO4 > 0.1 M NaClO4. In each of the studied systems there was observed a much larger increase in the (kts2) values compared to the (kts1) values when the concentration of TMTU was increased. A linear relationship between the rate constant of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Studies on the kinetics of various depolarisers in the presence of electrode substances are comprehensively discussed in the literature [5][6][7][8][9][10][11]. It was demonstrated that the structures of the inter-phase area caused by adsorption of organic compounds on the surface of mercury play a significant role in the mechanism of the cap-pair effect.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the kinetics of various depolarisers in the presence of electrode substances are comprehensively discussed in the literature [5][6][7][8][9][10][11]. It was demonstrated that the structures of the inter-phase area caused by adsorption of organic compounds on the surface of mercury play a significant role in the mechanism of the cap-pair effect.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structure of both organic substances having hydrophobic methyl groups allows us to expect that vertical orientation of their molecules may change insignificantly. The investigated substances have an inverse effect on the kinetics of electroreduction of Zn 2+ ions [16,17]. The adsorption parameters presented in the paper concerning the formation of mixed adsorption layers will be used in studies of kinetics and the mechanism of electroreduction of Zn 2+ ions in the presence of TB and TMTU.…”
Section: Introductionmentioning
confidence: 99%
“…Details concerning the determination of potentials of the outer Helmholtz plane (OHP), U 2 and the potential in the reaction plane, U r are described elsewhere [6,11]. Based on the command of the k f and U r values the true rate constants were appointed based on the dependence:…”
Section: Tablementioning
confidence: 99%
“…These compounds may have considerable effect on the rate of electrode processes. The accelerating effect of the adsorbed nonelectroactive species on the kinetics of electroreduction of many metal ions at mercury electrode was already discussed in the literature [1][2][3][4][5][6][7][8]. It is also well known that the labile adsorption of the accelerating substance and the active complex generated on the electrode surface are simultaneously responsible for the accelerating effect [9][10][11].…”
Section: Introductionmentioning
confidence: 99%